Structural Equation Modeling of Health Literacy, SelfEfficacy, Physical Activity, Dietary Pattern and Body Image in Obese Young Adults in Tomohon City - Jonesius Eden Manopo; Andi Zulkifly Abdullah; Citra Kesumasar; Ridwan Thaha Mochtar; Abdul Rahman Stang; Sirajuddin Saifuddin; Ridwan Amiruddin (Indian Journal of Forensic Medicine & Toxicology, 2021)
The prevalence of obesity is at a dangerous level. This situation is influenced by the extreme value of Tomohon city.This study aims to create Structural Equation Modeling of health literacy, self-efficacy, physical activity, dietarypattern and body image in obese young adults in Tomohon City and to analyze the influence between health literacy,self-efficacy, dietary pattern, physical activity and body image in obese young adults in Tomohon City. This researchis a non-experimental research with a quantitative approach. Sample were 161 adults, aged 20-30 years, andhad a total BMI ?25. Data analysis was carried out by testing the structural equation modeling using Smart PLS.The results showed that structural equation modally of health literacy, self-efficacy, physical activity, dietary patternand body image in this research can be used to show how strong the effect or influence of one variable was onanother variable. Based on the equation modeling, several variables have a weak and strong influence so that theeffect between variables also has different percentages.